Green Logistics : Enablers for Sustainable Development - Fransoo, Jan C. (World Bank, Washington, DC, 2014)
Logistics is the backbone of industry and commerce. As a discipline, it describes the management and coordination of activities along supply chains. These activities include freight transport, storage, inventory management, materials handling and related information processing. A large part of logistics activities are often outsourced to specialized providers that provide cost-effective services. Research has shown that, at least in high income economies, the value of services is not assessed in monetary and service quality terms alone. In making decisions, logistics professionals are increasingly taking into consideration external effects such as emissions, pollution, noise, and accidents. 'Green logistics' may not be an independent policy area. Rather, the supply chain perspective provides a framework to understand and deal with issues that are separate but ultimately interrelated. Importantly, looking at supply chains helps policy makers understand the interests and actions of private sector operators. 'Green logistics' may therefore propose a number of tools and identify emerging sustainable solutions contributing to the overarching objective of 'green growth.'